Lodo granular aeróbio (LGA): efeito de cátions divalentes e micropoluentes emergentes na formação, remoção, microbiologia e estabilidade operacional - Barros, Antônio Ricardo Mendes (2020)
Aerobic granular sludge (AGS) is one of the most recent technologies developed in the field of biological treatment of domestic and industrial effluents. Although AGS has physical, chemical, and microbiological properties that result in lower footprint, lower energy demand, and good efficiencies for simultaneous removal of C, N, and P, the technology still presents some problems in the formation and maintenance of granules, especially in long operating periods. Furthermore, little is known about the effects of emerging micropollutants presence in AGS systems, as well as their removal. In this perspective, this research evaluated the effect of divalent cations and emerging micropollutants (antibiotics and parabens) on the formation, removal, microbiology, and operational stability of AGS systems. In the first and second study, due to the lack of research with sequential batch reactors (SBR) for simultaneous fill/draw operated with low upflow speed of the liquid (1 m•h-1) with the reduction of sedimentation time, the effect of the addition of Ca2+ on the bonding between the negatively charged extracellular polymeric substances (EPS) and the microbial surface was investigated as well as whether coal ash of thermoelectric plants could act as a granulation core, source of cations, and abrasive element in AGS, respectively. It was observed that the addition of calcium and ash did not accelerate the formation of granules or improve the efficiency performance of the systems. The microbial structure, especially in terms of bioactivity, was also not affected. Possibly, the selection process, generated by the type of RBS used and the short sedimentation period, had a greater effect on the formation of granules than the presence of the divalent cation and the ashes, which were probably washed out of the system. In order to elucidate the operational differences on the effect of divalent cations in simultaneous fill/draw SBRs and conventional SBRs, a third study was conducted with four reactors in parallel, two with the addition of calcium and two as controls. In the control reactors without the addition of calcium, the SBR operation influenced sludge settleability, resulting in values of VSI30 < 30 mL•g-1 and VSI30/VSI5 > 0.9, for conventional SBR, and VSI30 between 50 and 60 mL•g-1 and VSI30 / VSI5 > 0.8, for simultaneous fill/draw SBR. For reactors supplemented with calcium, its addition decreased the granulation time, mainly in the conventional reactor, suggesting that the addition of divalent cations, such as calcium and magnesium, is more accentuated in conventional SBRs, in which the pressure of selection is greater. The fourth study evaluated the operational performance of the AGS technology in the treatment of synthetic wastewater containing parabens (200 µg•L-1 each) methylparaben (MeP), ethylparaben (EtP), propylparaben (PrP), and butylparaben (BuP). In addition to the impact of these compounds on the aerobic granulation process and on the stability of the granules cultivated in an SBR, the removal of organic matter, nutrients (N and P), and the parabens themselves was evaluated, for which possible removal mechanisms were also identified. Associated with this, the influence of parabens on the microbial activity of removing organic matter and nutrients (N and P) was also evaluated. In the presence of parabens, aerobic granules were developed with good settleability, but with a fragile and uneven structure due to the lower EPS production, which also affected the concentration of solids of the system. As to the removal efficiency of C, N, and P, there was no significant effect of parabens. Regarding the removal of parabens in AGS systems, high removal efficiencies were obtained (> 85%). Although parabens were partially removed in the anaerobic phase, the aerobic phase was mainly responsible for the removal of these compounds, most likely by cometabolism. While adsorption evidently did not contribute to the removal of ethylparaben (EtP), propylparaben (PrP), and butylparaben (BuP), it was the initial mechanism for removing methylparaben (MeP) (~57%), which was suggested as a probable intermediary of degradation of the other parabens studied. Under the same methodological aspects applied to parabens removal, the fifth study evaluated the removal of the antibiotics trimethoprim (TMP) and sulfamethoxazole (SMX) in AGS associated or not with the supplementation of the redox mediator anthraquinone-2,6-disulfonate (AQDS). When only the AGS performance was evaluated, removals of ~30%, for TMP, and ~60%, for SMX, were observed. However, when associated with AQDS, removals reached 75% for TMP and 95% for SMX. The increase of removal percentages may be associated with the catalytic action of the redox mediator in cometabolic processes.